Trading Partners: New Views on Theatre Translation in Canada - Nichols, Glen (TTR)

(untitled) (Association canadienne de traductologie, 2002)
AbstractWhat kinds of modern Canadian plays are most often translated or adapted for production elsewhere in Canada or overseas? How many modern Canadian plays are translations or adaptations of non-theatrical originals (novels, poetry, fairy tales)? Where can one find out if a translation of a Canadian play is available? These are among the questions addressed by the catalogue From Around the World and at Home: Translations and Adaptations in Canadian Theatre, the first comprehensive database of Canadian theatre translations. This paper examines the two basic questions of translation in Canadian theatre as revealed by the database, not from the usual point of view of one or several individual works looked at closely, but from the broader perspective of a large statistical overview:1. What is the state of theatre translation within the borders of Canada? That is, what transfers are happening between linguistic groups within Canada? And what role do inter-generic translations play here?2. Are there regional variations in terms of overseas influence? In other words, do different parts of Canada look to different parts of the world for theatrical sources?Published by Playwrights Union of Canada in 2001, the Catalogue contains over 3000 separate entries, including source and target references to Canadian plays translated for production or publication either inside or outside Canada, and Canadian plays which are themselves translations of other domestic or overseas pieces. With the term “translation” including generic as well as linguistic transfers, the Catalogue is designed to serve as both a reference source and the basis for more detailed analysis of the ongoing role of translation in Canadian theatre.